Anti-diabetic (AD) activities of ZnO doped with Ce (7 at%) nano particles (NP). (2020) - Kannan, K. Senthil; Velraj, Malarkodi; Flora, G.; Ilaiyaraja, K.; Kohila, S.
Abstract: ZnO doped with Ce7 at% nano particle is the application of nano materials and in many fields. The nano particles of ZnO doped with Ce 7 at% are prepared directly into nano form. The nano particle has antidiabetic activity because of ZnO and by Ce 7 at%. Then ZnO NPs are analysed by PXRD method for parameters and confirmed with earlier data. Nano particles which are used for antidiabetic study has inhibition values which are increased with proper increase in the value of concentration, IC50 values are 28.01 for nano particles of ZnO doped with Ce7 at%.